Analisis Pelaksanaan Pembelajaran Berdasarkan Karakteristik Siswa Sebagai Upaya Pencegahan Terjadinya Hal-Hal Yang Tidak Diinginkan Perilaku Di Sekolah Tahfiz Al Yusra Abadi - Alya Sarah Zaini HSB; Sahbuki Ritonga (Insan Zenius Ilmiah, 2024)
This research aims to analyze the implementation of learning about student characteristics to prevent undesirable behavior at Al Yusra Abadi Tahfiz School. The research method used is a qualitative approach with data collection techniques through literature review, observation, and interviews. The research results indicate that the application of learning methods based on the Quran and Hadith, such as memorization, talaq, and discussion, has a positive impact on students' character development. In addition, the pesantren environment and the intense interaction between students and teachers also play a crucial role in forming discipline, responsibility, and noble character. Factors that support the implementation of research include the availability of sufficient learning opportunities and the support of quality teachers. At the same time, several inhibiting factors exist, such as a lack of student motivation and challenges in consistently implementing teaching methods. In general, the effective implementation of the Al Yusra Abad Tahfiz learning can prevent negative behaviors and enhance the morals of the students, making them noble individuals who benefit society.